Prokaryotic Responses to Ammonium and Organic Carbon Reveal Alternative CO2 Fixation Pathways and Importance of Alkaline Phosphatase in the Mesopelagic North Atlantic - Federico Baltar (Centre for Ecology and Evolution in Microbial Model Systems, EEMiS, Linnaeus University); Daniel Lundin (Centre for Ecology and Evolution in Microbial Model Systems, EEMiS, Linnaeus University); Joakim Palovaara (Centre for Ecology and Evolution in Microbial Model Systems, EEMiS, Linnaeus University); Itziar Lekunberri (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Thomas Reinthaler (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Gerhard J. Herndl (Department of Limnology and Bio-Oceanography, Faculty of Life Sciences, University of Vienna); Jarone Pinhassi (Centre for Ecology and Evolution in Microbial Model Systems, EEMiS, Linnaeus University) (Frontiers in Microbiology, 2016)
The abstract is available here: https://uscholar.univie.ac.at/o:528071 The abstract is available here: https://uscholar.univie.ac.at/o:528071